URBAN SPACE REVITALIZATION IN POST-CONFLICT CITY WITH CULTURAL APPROACH PELA GANDONG IN AMBON - Civitaria Siahay, Margie (Sean Institute, 2022)
Ambon is a city hit by religious conflict many years ago (1999-2004). Although it has now been declared safe and conducive, it appears that the conflict is still felt, especially in community living spaces that have been patterned in accordance with their religious beliefs until now. Therefore, it affects the existence of the urban space (public space), which causes a decreased quality of the city environment. In the end, the segregation in the living area decreased the quality of urban space significantly. Urban space should be a public space used by the community as part of the public was not achieved well. Revitalizing urban space by focusing on the design is presented as a mediator between the two parties separated in this living space. Using the concept of shared space is expected to be able to restore the harmony of urban space, which can be mediation with the aim of uniting ethnic and religious diversity in the public space in the city of Ambon. The concept of shared space will bring back integrity and balance as well as the 'sense of place' in the downtown area, especially public space, and returns the identity of Ambon in the post-conflict period in order to become a space of togetherness among communities based on local wisdom, the bond of Pela-Gandong.